THE ROLE OF THE SCHOOL PRINCIPLE AS SUPERVISOR IN IMPROVING TEACHER PROFESSIONALITY RA NAWA KARTIKA VIII SIDOLAJU - Kuni, Fatonah (JOURNAL J-MPI : JURNAL MANAJEMEN PENDIDIKAN, PENELITIAN DAN KAJIAN KEISLAMAN, 2023)
The professionalism of a teacher cannot be separated from the principal's role as a supervisor. Where the task is to be fully responsible for supervising educators or teachers. The purpose of this study was to analyze the role of the principal as a supervisor in increasing teacher professionalism at RA Nawa Kartika VIII Sidolaju, Ngawi. This research method is a qualitative descriptive research. The results of this study indicate that the role of the principal as a supervisor to improve teacher professionalism has been well implemented. The conclusion from this study is that the role of the principal as a supervisor greatly determines the professionalism of teachers at RA Nawa Kartika VIII Sidolaju